Civil meanings of child abduction. Analysis of a real case with two parties: Spain (European Union) and Russia Federation - PizarroMoreno, Eugenio (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
There are not many occasions, neither from the investigative point of view nor from forensic practice, much less, as is the case, from both jointly, in which the jurist can study and try to resolve a case of child abduction. The male parent has British nationality; the mother is a national of the Russia Federation. However, it can be said that this history of doctrine and jurisprudence lacked the necessary investigative interest if there had not been a minor, born in Spain, and whom her mother, without the knowledge or consent of her father, transferred to Russia. Thus begins a case that took us to the Court of Justice of the European Union. And, of course, to this research article than shows that between the formulation of a law or rules and its execution, there is always a pervasive chasm that not everybody is able to cross or knows how to do so. Law is more a science of problems than of solutions, and it usually responds poorly -it cannot be otherwise- to facts with a markedly surprising nature.